2001
DOI: 10.1097/00043764-200112000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Depleted Uranium Exposed Gulf War Veterans: Health Effects Observed in an Enlarged ???Friendly Fire??? Cohort

Abstract: To determine clinical health effects in a small group of US Gulf War veterans (n = 50) who were victims of depleted uranium (DU) "friendly fire," we performed periodic medical surveillance examinations. We obtained urine uranium determinations, clinical laboratory values, reproductive health measures, neurocognitive assessments, and genotoxicity measures. DU-exposed Gulf War veterans with retained metal shrapnel fragments were excreting elevated levels of urine uranium 8 years after their first exposure (range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 14 publications
1
57
0
Order By: Relevance
“…This and subsequent work (McDiarmid et al 2000(McDiarmid et al , 2001(McDiarmid et al , 2004a(McDiarmid et al ,b, 2006 confirmed that urine U excretion is a good measure for quantifying systemic exposure to U in this cohort, as it serves as an indication of the extent to which U was being released to blood from embedded fragments and/or tissue stores of previously released, inhaled or ingested DU.…”
Section: Methods For Measuring Uranium Body Burden and Systemic Exposmentioning
confidence: 58%
“…This and subsequent work (McDiarmid et al 2000(McDiarmid et al , 2001(McDiarmid et al , 2004a(McDiarmid et al ,b, 2006 confirmed that urine U excretion is a good measure for quantifying systemic exposure to U in this cohort, as it serves as an indication of the extent to which U was being released to blood from embedded fragments and/or tissue stores of previously released, inhaled or ingested DU.…”
Section: Methods For Measuring Uranium Body Burden and Systemic Exposmentioning
confidence: 58%
“…This finding, however, was disputed by the National Academy of Science, and the possible association of DU with prolactin levels was not found during a subsequent reassessment (McDiarmid et al, 2001). …”
Section: Reproductive Issuesmentioning
confidence: 99%
“…These findings are consistent with medical records for US troops in the 1991 Gulf War (PAC, 2005) and Italian ground troops in the Balkan War (Italian Ministry of Defense, 2001). McDiarmid et al (2001), however, found an elevation in sister chromatid exchanges (SCE) for veterans with high DU concentrations in their urine relative to veterans with low DU concentrations. These observations are similar to observations for uranium workers showing an increase in SCE (Martin et al, 1991) with no statistically significant increase of cancers of any type (Waxweiler et al, 1983).…”
Section: Doses and Cancer Risksmentioning
confidence: 99%
See 2 more Smart Citations